2021
DOI: 10.3390/biology10100995
|View full text |Cite
|
Sign up to set email alerts
|

De novo Assembly and Analysis of Tissue-Specific Transcriptomes of the Edible Red Sea Urchin Loxechinus albus Using RNA-Seq

Abstract: Edible red sea urchin (Loxechinus albus) is an endemic echinoderm species of the Chilean coasts. The worldwide demand for high-quality gonads of this species has addressed the depletion of its natural populations. Studies on this sea urchin are limited, and genomic information is almost nonexistent. Hence, generate a transcriptome is crucial information that will considerably enrich molecular data and promote future findings for the L. albus aquaculture. Here, we obtained transcriptomic data of the edible red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Additionally, the expression patterns of specific conserved miRNAs in particular tissues and developmental stages indicated that they are involved in organ- and developmental stage-specific functions reported in other teleost [ 24 ]. To obtain as most complete as possible a first transcriptome of edible red sea urchin, Loxechinus albus was the objective of Antiqueo et al [ 25 ]. For this, the authors sequenced gonads, intestines, and coelomocytes of juvenile urchins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the expression patterns of specific conserved miRNAs in particular tissues and developmental stages indicated that they are involved in organ- and developmental stage-specific functions reported in other teleost [ 24 ]. To obtain as most complete as possible a first transcriptome of edible red sea urchin, Loxechinus albus was the objective of Antiqueo et al [ 25 ]. For this, the authors sequenced gonads, intestines, and coelomocytes of juvenile urchins.…”
mentioning
confidence: 99%
“…After de novo assembly, a total of 185,239 transcripts were obtained, of which 57,106 (31%) were successfully annotated. Comparative transcriptome analyses revealed that differentially expressed transcripts among tissues were specialized in different biological processes according to the specific functions of these tissues [ 25 ].…”
mentioning
confidence: 99%